PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN GAYA KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA (STUDI PADA PT. ASDP INDONESIA FERRY (PERSERO) CABANG SAPE) - Lakahing, Marthen Yacob; Widodo, Sri (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
This study aims to determine the effect of transfomational leadership style and transactional leadershipstyle on performance (Study at ASDP Indonesia Ferry Limited Company, Sape Branch). This research uses aquantitative approach with a survey method. The total population of 70 ship crews on decks and machines,with saturated sampling techniques. Data collection using a questionnaire with a Likert scale of 1 to 5.Method of data analysis using multiple linear regression tests, with partial and simultaneous hypothesis testproceeded using SPSS program version 24.0. The results showed that: 1) the transformational leadershipstyle partially had a positive and significant effect on performance; 2) Transactional leadership stylepartially has a positive and significant effect on performance; 3) Transformational leadership style andtransactional leadership style simultaneously have a positive and significant effect on performance.Keywords: Transformational Leadership Style, Transactional Leadership Style, Performance